CD4 T Cell Dependent Colitis Exacerbation Following Re-Exposure of Mycobacterium avium ssp. paratuberculosis - Suwandi, Abdulhadi; Bargen, Imke; Pils, Marina C.; Krey, Martina; Zur Lage, Susanne; Singh, Anurag K.; Basler, Tina; Falk, Christine S.; Seidler, Ursula; Hornef, Mathias W.; Goethe, Ralph; Weiss, Siegfried (Frontiers in Cellular and Infection Microbiology, 2017)
Mycobacterium avium ssp. paratuberculosis (MAP) is the causative agent of Johne’s disease (JD), a chronic inflammatory bowel disease of cattle characterized by intermittent to chronic diarrhea. In addition, MAP has been isolated from Crohn’s disease (CD) patients. The impact of MAP on severity of clinical symptoms in JD as well as its role in CD are yet unknown. We have previously shown that MAP is able to colonize inflamed enteric tissue and to exacerbate the inflammatory tissue response (Suwandi et al 2014). In the present study, we analyzed how repeated MAP administration influences the course of dextran sulfate sodium (DSS)-induced colitis. In comparison to mice exposed to DSS or MAP only, repeated exposure of DSS-treated mice to MAP (DSS/MAP) revealed a significantly enhanced clinical score, reduction of colon length as well as severe CD4+ T cell infiltration into the colonic lamina propria. Functional analysis identified a critical role of CD4+ T cells in the MAP-induced disease exacerbation. Additionally, altered immune responses were observed when closely related mycobacteria species such as M. avium ssp. avium and M. avium ssp. hominissuis were administered. These data reveal the specific ability of MAP to aggravate intestinal inflammation and clinical symptoms. Overall, this phenotype is compatible with similar disease promoting capabilites of MAP in JD and CD.